2008
DOI: 10.1002/biof.5520320121
|View full text |Cite
|
Sign up to set email alerts
|

Functions of coenzyme Q10 in inflammation and gene expression

Abstract: Clinical studies demonstrated the efficacy of Coenzyme Q10 (CoQ10) as an adjuvant therapeutic in cardiovascular diseases, mitochondrial myopathies and neurodegenerative diseases. More recently, expression profiling revealed that Coenzyme Q10 (CoQ10) influences the expression of several hundred genes. To unravel the functional connections of these genes, we performed a text mining approach using the Genomatix BiblioSphere. We identified signalling pathways of G-protein coupled receptors, JAK/STAT, and Integrin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
145
1
6

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 234 publications
(158 citation statements)
references
References 15 publications
6
145
1
6
Order By: Relevance
“…Studies have suggested that CoQ10 also exerts anti-inflammatory properties via NFκB1-dependent gene expression [21]. Because this is a common pathway for periodontal inflammation, even this could be the possible mechanism for reduction in gingival inflammation due to CoQ10 supplementation.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have suggested that CoQ10 also exerts anti-inflammatory properties via NFκB1-dependent gene expression [21]. Because this is a common pathway for periodontal inflammation, even this could be the possible mechanism for reduction in gingival inflammation due to CoQ10 supplementation.…”
Section: Discussionmentioning
confidence: 99%
“…Doring et al [23] and Schmelzer et al [24] Page 19 of 42 [53]. In another study, anti-inflammatory properties of CoQ10 on serum CRP levels of baboons have also been observed, but only when combined with vitamin E. This modification of serum CRP level was associated with an increase blood total antioxidant status [54].…”
Section: Page 16 Of 42mentioning
confidence: 91%
“…CoQ10 is also involved in oxidative phosphorylation as an electron transporter and is therefore involved in energy homeostasis [17][18][19][20]. Data obtained in vitro even suggest its antiinflammatory potency [21][22][23][24][25]. However, the effect of CoQ10 given orally remains only poorly explored in the context of obesity and diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…A human clinical study investigating the relation between CoQ 10 and inflammation in patients with coronary artery disease reports that oral supplementation of CoQ 10 at 150 mg/day results in decreased expression of inflammatory markers, that is, C-reactive protein, IL-6, and homocysteine (Lee et al, 2012b). Furthermore, data collected from human and rodent cellular models show that CoQ 10 affects gene expression and inhibits the release of IL-6 and TNF-α, consistent with its anti-inflammatory effects (Schmelzer et al, 2007(Schmelzer et al, , 2008. Far less convincing benefits are reported for neurodegenerative diseases, such as PD (Shults and Haas, 2005;Shults et al, 2002;Villalba et al, 2010).…”
Section: Introductionmentioning
confidence: 91%